PENINGKATAN HASIL BELAJAR IPAS DENGAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTU PETA DIGITAL PADA KURIKULUM MERDEKA - Suskarjanti; Meirza Nanda Faradita; Iswahyuni (PROCEEDING UMSURABAYA, 2024)
This study aims to improve the learning outcomes of reading maps of Natural and Social Sciences (IPAS) subjects in grade IV students through the implementation of the Problem Based Learning (PBL) model. This research method is Classroom Action Research (PTK) involving 18 students as research subjects. The instruments used were pre-test and post-test written test sheets to evaluate the success of learning. The results showed an increase of 33% from cycle I to cycle II. In this study, teachers used Google Earth digital map media to help students learn to read maps. The implementation of the Problem Based Learning (PBL) model succeeded in improving students' learning outcomes because this model directs students to be able to collaborate with their groupmates to solve a problem in the task. The results of this study provide positive benefits for students to know their home address completely and show it on a digital map. Hence, the understanding of the name of the location where the students live increases